Workload Intensity, Job Satisfaction, and Work Performance of University Clerk Employees at Kalinga State University: Basis for a Capacity-Building Program - Dayag, Sheila Lyn (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined workload intensity, job satisfaction, challenges, and work performance among college clerk employees at Kalinga State University as basis for a capacity-building program. Anchored on quality service delivery, records life cycle principles, and organizational support, the study used a descriptive-correlational research design involving 38 clerical staff and 38 immediate supervisors from the Bulanao and Dagupan campuses. Data were gathered through a structured questionnaire, supplemented by interviews and document review, and analyzed using descriptive statistics, Kruskal-Wallis Test, Pearson’s correlation coefficient, and thematic analysis. Findings revealed that clerical staff experienced a very high level of workload intensity, particularly in documentation, records processing, and peak-period academic demands. Despite this, they reported a high level of job satisfaction, while supervisors rated their work performance very highly in terms of professionalism, accuracy, efficiency, and reliability. Documentation and records overload emerged as the most pressing challenge. Most demographic variables showed no significant differences in workload intensity, job satisfaction, challenges, and performance, except civil status in relation to job satisfaction. Pearson correlation results showed no significant relationship among workload intensity, job satisfaction, and challenges. The study concludes that clerical staff remain effective and satisfied despite heavy workload demands, but institutional interventions are needed to reduce workload pressure and sustain performance. Recommended actions include additional staffing, improved ICT infrastructure, a fully integrated Student Information System, regular training, clearer workload policies, stronger administrative and technical support, and better office resources. The study supports SDG 4 on Quality Education, SDG 8 on Decent Work and Economic Growth, SDG 9 on Industry, Innovation and Infrastructure, and SDG 16 on Peace, Justice, and Strong Institutions. Its sustainability impact lies in strengthening academic records management, improving institutional efficiency, supporting employee well-being, and promoting accountable, technology-supported, and reliable university service delivery.